2007
DOI: 10.1007/s12010-007-9217-1
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale purification of human granulocyte-macrophage colony-stimulating factor expressed in Bombyx mori pupae

Abstract: Human granulocyte-macrophage colony-stimulating factor (hGM-CSF) acts on many different kinds of cells, including monocytes, macrophages, granulocytes, eosinophils, and multipotential stem cells. To explore further explore pharmaceutical action, we expressed hGM-CSF by the Bombyx mori nucleopolyhedrovirus expression system in silkworm pupae. However, purifying recombinant proteins from silkworm pupae on a large scale has been a big challenge. To establish purification methods suitable for mass production, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The purified rhGM-CSF expressed by the silkworm pupae bioreactor was produced in our laboratory . The human GM-CSF ELISA kits were obtained from Beijing 4A Biotech Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The purified rhGM-CSF expressed by the silkworm pupae bioreactor was produced in our laboratory . The human GM-CSF ELISA kits were obtained from Beijing 4A Biotech Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, solid ammonium sulfate was slowly added to the SLP solution to a final concentration of 25%, and the resulting mixture was stirred at 4 °C for 2 h. Next, the solution was centrifuged at 12000 g at 4 °C for 30 min. The supernatant was adjusted to 65% (NH 4 ) 2 SO 4 , and the precipitated proteins were pelleted . The resulting pellet was resuspended in an appropriate volume of PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was purified and determined to have molecular weigh of 29 kDa [7], [10], [11]. It's post-translational modifications were characterized in addition to its glycosylation [7], [10], [11]., The oral formulation of BmrhGM-CSF was used in our previous animal study. The results from preclinical studies demonstrated that orally administered BmrhGM-CSF could function as an active cytokine [10].…”
Section: Introductionmentioning
confidence: 99%